The Role of General Moderate Cooling in Learning Process of Animals with Different Type of Nervous System Excitability - Nikishkova, I. N. (Problems of Cryobiology and Cryomedicine, 2004)
The results of studying the possibility of a modulating effect of an organism’s general moderate cooling on the learning process course in the model of active avoidance behaviour (AAB) formation in animals of different age are shown. The results of the work allow to consider a preliminary general moderate cooling as a contributing to more successful AAB formation and preventing the adaptive behaviour pathologies, occurring in animals. The age peculiarities of this cooling effect are demonstrated as well.